Low-radiation of technetium-99m-sestamibi and single-photon emission computed tomography/computed tomography to diagnose parathyroid lesions - Vaiman, Michael; Cohenpur, Mehrzad; Halevy, Ariel; Volkov, Olga; Gold, Ruth; Peer, Michael; Golan, Haim; Gavriel, Haim (World Journal of Nuclear Medicine, 2019)
We compared preoperative regular activity and low-activity radiology-based predictions with real surgical and pathological findings for parathyroidectomy surgery. The study retrospectively analyzed 54 consecutive cases (2009–2016) for benign tumor removal. Technetium-99m (Tc-99m)-sestamibi was used as a diagnostic radiopharmaceutical for diagnostic dual-phase parathyroid scintigraphy and single-photon emission computed tomography/computed tomography. We assessed images obtained with the radiation activity of 925 megabecquerel (MBq) and images obtained with the activity of 185 MBq. The study compared preoperative evaluation of tumor presence, multiplicity, location, and the type of pathology with actual data that were revealed during the operation and pathological investigation. The agreement between preoperative radiological prediction and actual location, number, and type of the parathyroid lesions was achieved in 98.4% (n = 61/62 lesions). The agreement between 925 MBq-based and 185-MBq based investigations was 100%. The agreement between radiological and pathological findings was 100% for both investigations. Our data suggest that the radioactivity of 185 MBq applied in the evaluation of the parathyroid glands provides results similar to the currently used 925–1110 MBq if used for diagnostic dual-phase parathyroid scintigraphy with Tc-99m-sestamibi. Such radioactivity may reduce the exposure to radiation of the patients and the staff without compromising results of the investigation.
Keywords: Parathyroid glands; parathyroidectomy; scintigraphy; Tc-99m-sestamibi